Intelligent collision avoidance based on two-dimensional risk model. Issue 3 (September 2016) - Liang, Yan-hua; Cai, Chengtao
The collision avoidance and path planning technology is an important issue for submarine research field. It is essential and crucial for submarine to navigate underwater safely. There are lots of drawbacks for ensuring this important mission. For handling with the challenging and imperative issue, a novel and efficient collision risk model is proposed. A serial of motions of the submarine to be processed for fulfilling the collision avoidance based on this approach. The concepts of detection domain and fuzzy logic are adopted for modeling the degree of collision risk. The detection domain is used as the submarine safety scope when navigating underwater while the fuzzy logic is used as the mathematical implement for the analysis and synthesis of relations between obstacles or other submarines that are met in the navigation environment. The collision risk is regarded as one effective evaluation function that reflects which exact action should be done when the threshold of the risk degree is met. In order to verify the performance of proposed method, multisubmarines simulation experiments are concluded in different scenarios.